2022
DOI: 10.3390/medsci10040069
|View full text |Cite
|
Sign up to set email alerts
|

T-Peak to T-End Interval for Prediction of Positive Response to Ajmaline Challenge Test in Suspected Brugada Syndrome Patients

Abstract: Background: Brugada syndrome (BrS) is diagnosed in patients with ST-segment elevation with coved-type morphology in the right precordial leads, occurring spontaneously or after provocative drugs. Due to electrocardiographic (ECG) inconsistency, provocative drugs, such as sodium-channel blockers, are useful for unmasking BrS. Ajmaline is superior to flecainide and procainamide to provoke BrS. Prolonged T-peak to T-end (TpTe) is associated with an increased risk of ventricular arrhythmia and sudden cardiac death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…In BS, the ajmaline challenge is performed to provoke BS, and there was research investigating whether prolonged Tp-e or the corrected interval can predict the positive result of the ajmaline challenge. However, its role declined [ 114 ]. Other studies revealed a significant correlation between Tp-e prolongation and the occurrence of life-threatening arrhythmic events among patients with BS [ 115 , 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…In BS, the ajmaline challenge is performed to provoke BS, and there was research investigating whether prolonged Tp-e or the corrected interval can predict the positive result of the ajmaline challenge. However, its role declined [ 114 ]. Other studies revealed a significant correlation between Tp-e prolongation and the occurrence of life-threatening arrhythmic events among patients with BS [ 115 , 116 ].…”
Section: Resultsmentioning
confidence: 99%